Hydrometeorological Disaster Risk Reduction Mitigation in Johan Pahlawan District, West Aceh District - Musliyadi, Musliyadi; Samsuddin, Samsuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Disaster Mitigation is a series of efforts to reduce disaster risk reduction, both through physical development as well as awareness and capacity building in dealing with disaster threats. Hydrometeorological disaster is one type of disaster that occurs in Indonesia, especially in Aceh which is affected by changes in weather. Now, La Nina has begun, namely a decrease in sea surface temperature due to changes in world temperature that occur on the surface of the East and Central Pacific Oceans which can form clouds that have the potential to cause rain and there is also an opportunity for Elnino to occur, namely rising sea surface temperatures, due to these weather changes. will cause several other types of disasters such as landslides, strong winds, drought, forest fires. All kinds of disasters that occur cannot be separated from the actions of human hands, as Allah has explained in the Qur'an in the letter Ar-Rum verse 41 which means that damage has appeared on land and at sea caused by the actions of human hands, so that Allah will feel some of them from the consequences of their actions, so that they return to the right path. From this verse, Allah has explained that the damage is the result of human activity, so humans must be aware of their actions. This study took place in the District of Johan Pahlawan, West Aceh Regency. The Johan Pahlawan sub-district was chosen as the research location because the sub-district has 21 villages, most of which are located very close to the sea and most of the villages in this area often experience the threat of hydrometeorological disasters.This study uses a qualitative method using a phenomemological approach, namely based on experiences that occur in an area and literature studies with various relevant fields as well as conducting interviews with people living in villages who often encounter the threat of hydrometeorological disasters. The results showed that all respondents who were used as samples had various levels of knowledge ranging from very low, low and high to knowledge of hydrometeorological disasters.